ANXIETY AND DEPRESSION IN PATIENTS WITH TINNITUS - Khan, Sikandar Ali; Raza, Maqbool; Farooq, Shahid; Tariq, Muhammad; Chandio, Muzafar; Rafique, Atif (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the presence and severity of depression and anxiety in patients with tinnitus.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at department of Psychiatry, Combined Military Hospital Multan in collaboration with ENT department, Combined Military Hospital Multan, from Sep 2019 to Mar 2020.Methodology: All diagnosed cases of tinnitus in ENT out-patient department Tinnitus Handicap inventory (THI) was applied to assess the severity of tinnitus. Diagnosis of depression and Anxiety was done based on diagnostic criteria of ICD10 of WHO and symptom severity was assessed using Beck Depressive Inventory (BDI) for depression and Beck Anxiety Inventory (BAI) for Anxiety.Results: A total of 88 participants were included in this study. Fifty-three (60.2%) were male, 35 (39.7%) were females. Twentythree (20.2%) ranged between 18-40 years of age, 65 (57.2%) participants ranged between 41-60 years of age. Seven (12.5%) participants scored less than 38 on tinnitus handicap inventory showing mild severity of tinnitus, 3 (5.3%) individuals scored moderate while 19 (33.9%) had severe level of tinnitus. Thirty-three (37%) participants had depression 55 (62%) out of total 88 participants had anxiety.Conclusion: Studies show presence of anxiety and depression in patients with tinnitus so it seems prudent to screen all patients of tinnitus for psychiatric co morbidity. A multidisciplinary approach is required for the treatment of patients with tinnitus so that physical as well as psychiatric/psychological management of these patients is provided well in time.